Comparison of the safety and immunogenicity of an MF59®-adjuvanted with a non-adjuvanted seasonal influenza vaccine in elderly subjects - Frey, Sharon E.; Reyes, Mari Rose Aplasca-De Los; Reynales, Humberto; Bermal, Nancy Nazaire; Nicolay, Uwe; Narasimhan, Vas; Forleo-Neto, Eduardo; Arora, Ashwani Kumar (Vaccine, 2014)
•Non-adjuvanted influenza vaccines elicit a poor response in the elderly.•Adjuvanted and non-adjuvanted vaccines were compared in 7082 elderly subjects.•Adjuvanted influenza vaccine elicited a significantly higher antibody response.•Adjuvant enhanced antibody responses in subjects with underlying medical conditions.•Adjuvanted vaccine had significantly higher response against heterologous A strains. Adjuvanted influenza vaccines can overcome the poor antibody response of conventional non-adjuvanted vaccines in the elderly. We evaluated the immunogenicity, safety and clinical effectiveness of an MF59®-adjuvanted trivalent influenza vaccine (aTIV) compared with a non-adjuvanted vaccine (TIV) in subjects ≥65 years old, with or without co-morbidities. In 2010–2011, subjects (N=7082) were randomized to receive one dose of aTIV or TIV. Co-primary objectives were to assess lot-to-lot consistency of aTIV, non-inferiority, superiority and immunogenicity 22 days after vaccination. Clinical effectiveness, reactogenicity and serious adverse events were monitored up to Day 366. The immunological equivalence of three lots of aTIV was demonstrated. aTIV was not only non-inferior to TIV but also elicited significantly higher antibody responses at Day 22 than TIV against all homologous and heterologous strains, even in subjects with co-morbidities. Superiority was not established. Reactogenicity was higher in the aTIV group, but reactions were mild to moderate and transient. aTIV elicited a significantly higher antibody response than TIV, especially against A/H3N2 strains, although superiority by pre-defined criteria was not formally met. The study demonstrates potential immunological benefits of MF59-adjuvanted influenza vaccines for the elderly. This trial was registered with www.clinicaltrials.gov (NCT01162122).